The Effect of Low Energy Ion Implantation on MoS2. (1st January 2016) - Murray, Ryan; Haynes, Katherine; Zhao, Xueying; Perry, Scott; Hatem, Christopher; Jones, Kevin
Abstract : The use of ultra low energy ion implantation is investigated as a doping method for MoS2 . 200 eV Cl and Ar implants at doses between 1 × 10 13 and 1 × 10 15 cm −2 were introduced into exfoliated MoS2 flakes. XPS results for Cl implants show a decrease in core peak binding energies for Mo3d and S2p with increasing dose, implying a p-doping effect. Implantation of MoS2 device channel regions is shown to reduce the channel's conductivity. However, isolated implantation of the contact region with low doses (1 × 10 13 cm −2 ) of Cl and Ar are shown to improve output characteristics by linearizing the IDS -VDS curves and by increasing current through the device. Cl was shown to be more effective than Ar at increasing the current, implying there is a potential chemical effect as well as damage effect. For higher doses (≥ 1 × 10 14 cm −2 ), the current through the device is reduced with increasing dose for both implant species. This report presents the as-implanted, unannealed results. Post-implantation anneals may be necessary to activate the dopants and fully realize the potential of this doping method.